Deskripsi Pengelolaan Motivasi Belajar Peserta Didik oleh Guru Kelas IV SDN 15 Sungai Raya - Azizah, Syarifah; Setyowati, Dessy; Afryaningsih, Yunika (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by preliminary observations that showed low levels of active participation, interest in learning, and engagement among students in class IV-B at SDN 15 Sungai Raya. These conditions prompted the need for a study on how teachers manage student motivation in the classroom. This study aims to describe how teachers manage student learning motivation in class IV-B. The study uses a qualitative descriptive approach with data collection through observation and interviews with teachers and students. The data were analyzed through data reduction, data presentation, and conclusion drawing stages. The results of the study show that teachers have been able to manage most aspects of student learning motivation well, including the desire and will to succeed, motivation to learn, future expectations, appreciation for learning, and interesting learning activities. However, the conducive learning environment aspect still needs to be improved so that students are more focused and comfortable during the learning process. Overall, the implementation of varied, interactive learning strategies that are tailored to student characteristics contributes positively to increasing learning motivation in the classroom